Male perspective on induced abortion - Duarte, Graciana Alves; Alvarenga, Augusta Thereza de; Osis, Maria José M Duarte; Faúndes, Aníbal; Hardy, Ellen (Revista de Saúde Pública, 2002)
OBJECTIVE: To analyze the perspective on induced abortion of men of a university community living in legal or consensual wedlock. METHODS: A descriptive cross-sectional study was carried out and 361 members of different categories of an university were interviewed. Chi-square test was used to assess the association between dependent and independent variables. RESULTS: Fifth-three percent of the participants acknowledged that women have the right to end pregnancy. Men were more favorable to abortion when there is a risk to woman's life (85%); rape-related pregnancy (80%); and fetal anomalies (75%). Higher schooling of both men and their partners and the interviewees' position (teacher/student) were associated to a positive attitude towards abortion. CONCLUSIONS: Men tended to be more prone to abortion in legally and/or socially accepted instances. Better education of both men and their partners was relevant to determine their attitude towards abortion.